The Level of Heavy Metal Contamination in Selected Vegetables and Animal Feed Grasses Grown in Wastewater Irrigated Area, around Asmara, Eritrea - Goitom Kfle; Ghebray Asgedom; Tedros Goje; Felema Abbebe; Lula Habtom; Hagos Hanes (Journal of Chemistry)
Soils irrigated with wastewater are by and large contaminated with heavy metals, and consumption of vegetables and animal feed grasses grown in contaminated soils have been a major food chain route for human exposure and pose a health hazard. A study was conducted in three sites to assess the accumulation of heavy metals in farms irrigated with wastewater between two and five decades in and around Asmara, Eritrea. The concentrations of metals (Al, Cd, Co, Cr, Cu, Fe, Mn, Mo, Pb, V, and Zn) in soils and plants (Medicago sativa L., Avena sativa L., Cynodon dactylon L., Corchorus olitorius L., and Cynara scholymus L.) grown in the farms were analyzed using an inductively coupled plasma optical emission spectrophotometer (ICP-OES). Multivariate analysis, such as principal component analysis (PCA) and cluster analysis (CA), was performed on the distribution of elements in plant species to identify the source of the heavy metals. The level of the metals in the soil samples was in the order of Mo < Cd < Co < Cu < Pb < V < Cr ≈ Zn < Mn < Fe < Al. The order of the metals in the plants of the different sites has been, in general, Cd < Co < V < Cr < Pb < Cu < Zn < Mn < Al < Fe. The study revealed that the soil samples of the studied sites were unsafe for agricultural purposes with respect to Fe, Mn, and Pb except for Pb in the case of the soil sample from the Kushet area. The levels of most of the studied heavy metals in the vegetation samples from all the sites were found within the FAO/WHO permissible limit. Al and Fe exceeded the FAO/WHO permissible limit with the exception of all plant samples from the Kushet area and M. sativa from Paradizo. The concentration of Al was also below the limit in C. dactylon from Adi-Segdo and Paradizo. Of the five vegetation considered in this study, C. olitorius was found to be a good accumulator and C. dactylon, the lowest accumulator of heavy metals. Based on the results of this study, the grass species C. olitorius should be further investigated for its phytoremediation capability of contaminated soils. The results of the multivariate analysis revealed that Fe, V, Al, Cr, Co, and Pb were controlled by mixed (natural and anthropogenic) sources and Zn, Mo, Cu, Mn, and Cd originated from the anthropogenic source. Very limited and inadequate studies were conducted on the accumulation of heavy metals in plants grown in wastewater irrigated farms around Asmara. Therefore, the results of this study are expected to shed light on the understanding of the community and enable the City Council to monitor the environmental quality and take appropriate actions.